2020
DOI: 10.1016/j.jhep.2020.01.026
|View full text |Cite
|
Sign up to set email alerts
|

HDL-related biomarkers are robust predictors of survival in patients with chronic liver failure

Abstract: Stable cirrhosis 228 patients enrolled at Medical University of Graz Acute decompensation 280 patients enrolled in CANONIC cohort including 107 patients with ACLF Measurement of HDL-related biomarkers (HDL-C, apoA-I) at baseline Highlights HDL levels are profoundly decreased in chronic liver failure. HDL-related biomarkers (HDL-C, apoA-I) are robust predictors of disease progression and survival. The prognostic value of single HDL-related biomarkers is very similar to that of the composite scores. HDL-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 44 publications
(45 reference statements)
3
66
1
Order By: Relevance
“…ApoA1 is the main stabilizing apolipoprotein of HDL (34). ApoA1 itself can deactivate bacterial endotoxins and mitigate the TNF-alpha production after LPS or LTA exposure (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…ApoA1 is the main stabilizing apolipoprotein of HDL (34). ApoA1 itself can deactivate bacterial endotoxins and mitigate the TNF-alpha production after LPS or LTA exposure (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol efflux capacity is markedly impaired in septic patients 29,30 and physical inactivity, inadequate exercise and an overall sedentary lifestyle are associated with impaired immune response 31 and increased risk of viral infections 31 and sepsis 32,33 . Low levels of HDL-cholesterol and low-density lipoprotein-cholesterol are associated with poor clinical outcomes and increased risk of infectious disease and survival, respectively [34][35][36] , while in critically ill and especially in septic patients, a reduction in lipid and lipoprotein levels has been well documented 37 , in particular apoA-I, apoA-II 15,30 , HDL and low-density lipoprotein 30,38,39 . Prolonged bedrest increases the risk of hospital-acquired pneumonia, which is often caused by bacterial infection 3 .…”
Section: Discussionmentioning
confidence: 99%
“…More recently it has been also shown that baseline levels of HDL were significantly lower in patients with stable cirrhosis than in healthy subjects, and this predicted the development of liver-related complications independently of MELD score. 15 In experimental models, as well as in patients with severe cirrhosis, recombinant HDL infusion was able to reduce concentration of pro-inflammatory cytokines by neutralizing circulating LPS. 13,14 In order to investigate the mechanism(s) underlying the protective role exerted by HDL in iVP16-LXRα mice in vivo, we performed in vitro experiments by using cell lines of the two main liver cell phenotype involved in the release of pro-fibrogenic signals, ie KCs and hepatocyte,, 1,3,4 although a role of LSEC can also be hypothesized.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] In patients with stable cirrhosis, baseline levels of HDL were significantly lower compared to controls predicting the development of liver-related complications independently of MELD. 15 Despite these lines of evidence, HDL role in chronic liver diseases has not been fully elucidated and the use of currently available pan-LXR agonists (that activate both isoforms), induces hepatic steatosis and hypertriglyceridemia by LXRαmediated induction of sterol regulatory element-binding protein 1 (SREBP-1)c in hepatocytes. 4,16 Therefore, alternative strategies have been considered, especially in the field of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%